Potentiation by L-cysteine of the bactericidal effect of hydrogen peroxide in Escherichia coli. - Berglin, E H (1982)
Under anaerobic conditions an exponentially growing culture of Escherichia coli K-12 was exposed to hydrogen peroxide in the presence of various compounds. Hydrogen peroxide (0.1 mM) together with 0.1 mM L-cysteine or L-cystine killed the organisms more rapidly than 10 mM hydrogen peroxide alone. The exposure of E. coli to hydrogen peroxide in the presence of L-cysteine inhibited some of the catalase. This inhibition, however, could not fully explain the 100-fold increase in hydrogen peroxide sensitivity of the organism in the presence of L-cysteine. Of other compounds tested only some thiols potentiated the bactericidal effect of hydrogen peroxide. These thiols were effective, however, only at concentrations significantly higher than 0.1 mM. The effect of L-cysteine and L-cystine could be annihilated by the metal ion chelating agent 2,2'-bipyridyl. DNA breakage in E. coli K-12 was demonstrated under conditions where the organisms were killed by hydrogen peroxide.